Ti 3 C 2 MXenes nanosheets catalyzed highly efficient electrogenerated chemiluminescence biosensor for the detection of exosomes - Zhang, Huixin; Wang, Zonghua; Zhang, Qiuxia; Wang, Feng; Liu, Yang (Biosensors & bioelectronics, 2019)
Exosomes have been reported to play an important role in the anti-tumor immune response, tumor diagnosis and other processes, and are promising biomarkers for early cancer diagnosis. In this work, a sensitive electrogenerated chemiluminescence (ECL) biosensor was developed for detection of exosomes using aptamer modified two-dimensional material Ti C MXenes nanosheets as the ECL nanoprobe because of its large surface area, the excellent conductivity and catalytic properties. The exosomes can be high efficiently captured onto the electrode surface by an EpCAM protein recognized aptamer modified on the electrode surface. In addition, the ECL nanoprobe can also recognize the exosomes, and significantly enhanced the ECL signals of luminol. Based on this strategy, a highly sensitive ECL biosensor for MCF-7 exosomes detection was obtained. The detection limit is 125 particles μL , which was over 100 times lower than that of conventional ELISA method. The as prepared ECL biosensor was performed successfully for MCF-7 exosomes detection in the serum. This strategy provided a feasible, sensitive and reliable tool for the exosomes detection in exosomes-related clinical diagnostics.